Alignment of genetic and restriction maps of the photosynthesis region of the Rhodopseudomonas capsulata chromosome by a conjugation-mediated marker rescue technique. - Taylor, D P (1983)
The restriction map of a 46-kilobase fragment of the Rhodopseudomonas capsulata chromosome was aligned with the genetic map of the photosynthesis region of that chromosome by a marker rescue technique. Marker rescue was effected by mobilization of vectors bearing fragments of R. capsulata DNA from Escherichia coli to a set of R. capsulata mutants. Plasmids pDPT51 and pDPT55 were constructed to mediate the intergeneric mobilization of pBR322 derivatives, and a mutant of R. capsulata with improved intergeneric recipient activity was isolated. Four previously unmapped genes affecting bacteriochlorophyll synthesis and two genes affecting photochemical reaction center synthesis have been located by marker rescue. Some of the fragments of R. capsulata DNA are capable of vector-independent complementation, implying that promoters are located on these fragments. Other fragments complement only in one orientation of insertion in the vector, implying transcription from promotors on the vectors and thereby fixing the direction of transcription for those fragments. Still other fragments of DNA show rescue only via recombination between homologous plasmid-borne DNA fragments and chromosomal mutations. The physical dimensions of the genetic map are 3.0 megadaltons per map unit, which agrees with previous estimates based on the size of the R. capsulata gene transfer agent.